Cognitive bias in intelligence analysis : testing the analysis of competing hypotheses method - Whitesmith, Martha (Intelligence, surveillance and secret warfare., 2020)
This book critiques the reliance of Western intelligence agencies on the use of a method for intelligence analysis developed by the CIA in the 1990s, the Analysis of Competing Hypotheses (ACH).